Preparation method of thin-wall carbon nanotube
By combining sol-gel method and chemical vapor deposition method, thin-walled carbon nanotubes with large inner diameters were prepared, solving the problems of complex and high cost in the prior art, and achieving efficient mass production and wide application of thin-walled carbon nanotubes.
Patent Information
- Application Number
- CN202411812735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The method of preparing thin-walled carbon nanotubes in the prior art is relatively complex, with high cost, and cannot achieve mass production. The obtained carbon nanotubes have a small inner diameter and cannot be filled with other substances, which limits its application development.
The carbon nanotube catalyst precursor was prepared by the sol-gel method, and thin-walled carbon nanotubes were prepared by chemical vapor deposition. Nitrogen-containing hydrocarbon compounds were used as carbon sources to control the size and field emission performance of the catalyst particles to achieve efficient preparation of thin-walled carbon nanotubes.
The simple and low-cost preparation of thin-walled carbon nanotubes is realized, and the mass production can be achieved, and the obtained carbon nanotubes are large in diameter, suitable for filling other nanomaterials, expanding their application range.
Smart Images

Figure CN119637856A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanotubes, and in particular to a method for preparing thin-walled carbon nanotubes. Background Art
[0002] Thin-walled carbon nanotubes refer to carbon nanotubes with a thin-wall index δ ≥ 4, where the thin-wall index δ = D m / W(D m =W is the inner diameter of the carbon nanotube, and W is the wall thickness of the carbon nanotube). Due to its larger inner diameter, thin-walled carbon nanotubes can be used in hydrogen storage materials, catalyst carriers, etc., and combined with the oxidation resistance and thermal stability of carbon nanotubes, functional nanocomposites with specific uses can be obtained, which are widely used in energy storage, electronic components, etc.
[0003] At present, the method for preparing multi-walled carbon nanotubes is simple and low-cost, and carbon nanotubes with large inner diameters of 20-40nm can be prepared. However, due to the influence of the number of tube wall layers, the thicker tube wall cannot meet the requirements of thin-walled carbon nanotubes, and the hollow structure is difficult to use. The method for preparing single-walled carbon nanotubes and few-walled carbon nanotubes (double-walled or triple-walled carbon nanotubes) can achieve the preparation of thin-walled carbon nanotubes, but the method for preparing single-walled and few-walled carbon nanotubes is relatively complicated and costly, which is not conducive to mass production; and the inner diameter of the carbon nanotubes prepared by the method is less than 5nm, which is not enough to fill other substances, such as: larger-sized nanomaterials, and thus it is impossible to prepare carbon nanotube composite materials with specific uses based on carbon nanotubes. The above defects have significantly limited the application and development of thin-walled carbon nanotubes.
[0004] Therefore, it is necessary to develop a method for preparing thin-walled carbon nanotubes that is simpler, lower in cost, and can be mass-produced, so as to fully utilize the advantages of the hollow structure of thin-walled carbon nanotubes and play an important role in expanding the application of thin-walled carbon nanotubes. Summary of the invention
[0005] The present invention overcomes the shortcomings of the prior art methods for preparing thin-walled carbon nanotubes, such as being relatively complex and costly, being unable to achieve mass production, and being unable to fill other substances if the inner diameter of the obtained carbon nanotubes is small, thereby making it impossible to prepare carbon nanotube composite materials with specific uses, and provides a method for preparing thin-walled carbon nanotubes.
[0006] The technical solution adopted by the present invention to achieve its invention object is: a method for preparing thin-walled carbon nanotubes, comprising the following steps:
[0007] S1. Preparing carbon nanotube catalyst precursor by sol-gel method;
[0008] S2, reducing the carbon nanotube catalyst precursor prepared in step S1 to obtain a carbon nanotube catalyst;
[0009] S3, using the carbon nanotube catalyst obtained in step S2 to prepare thin-walled carbon nanotubes by chemical vapor deposition;
[0010] In the step S1, the prepared carbon nanotube catalyst precursor is a metal oxide;
[0011] In the step S3, when the carbon nanotubes are prepared by chemical vapor deposition, the carbon source used is: nitrogen-containing hydrocarbon compounds.
[0012] The beneficial effects of the present invention are as follows: (1) When preparing carbon nanotube precursors, the advantages of using the sol-gel method include: a. The sol-gel method can ensure that each active component is evenly distributed in the carrier, and the amount of each component can be accurately controlled to ensure the activity of the catalyst particles. b. In the sol-gel method, the metal elements and organic substances are fully complexed, and the obtained colloid is stable, which is conducive to the subsequent preparation of catalyst particles with a stable crystal phase and uniform particle size. c. The product obtained by the sol-gel method has a high purity, which is conducive to ensuring the purity of the final product of the present invention. d. The sol-gel method is relatively simple, does not require complex equipment, has low cost, and is easy to industrially produce.
[0013] (2) The present invention uses a sol-gel method to fully complex metal ions with organic matter and ensure that the metal ions are evenly dispersed. After oxidation and calcination, the crystal form of the oxide can be well preserved, retaining the catalyst activity and specific properties, and obtaining: a metal oxide with a stable crystal phase and a large specific surface area, namely: the carbon nanotube catalyst precursor of the present invention.
[0014] (3) The present invention first prepares metal oxides and then reduces them. During the reduction process, oxygen atoms are decomposed, the gaps between metals increase, and the cone angles of metal particles also increase, both of which contribute to the thickening of the diameter of carbon nanotubes in the subsequent catalytic growth of carbon nanotubes. In addition, the carbon nanotube catalyst obtained by this process has high purity, stable crystal phase, and large specific surface area.
[0015] (4) The present invention first prepares the metal oxide and then reduces it, and also has the following application advantages: when the carbon nanotube catalyst is used to prepare carbon nanotubes by CVD method, the enthalpy value and growth time of the endothermic decomposition of the carbon source during the growth of the carbon nanotubes can be reduced. Compared with directly using the metal oxide as the carbon nanotube catalyst, under the same heat and time, the carbon nanotube catalyst of the present invention can achieve surface carbon coating faster to form carbon nanotubes.
[0016] (5) When preparing carbon nanotubes by chemical vapor deposition, based on the size of the carbon nanotube catalyst and using nitrogen-containing hydrocarbon compounds as the carbon source, the carbon nanotube catalyst particles can maintain a bottom growth mode during the growth of carbon nanotubes; and because the nitrogen-containing hydrocarbon compounds decompose at high temperatures, the nitrogen element in them can change the field emission properties of the catalyst metal particles, making it easier for the carbon nanotubes grown on the catalyst particles to grow in the direction of a larger helical angle, thereby avoiding the process of thickening the parallel wall layer and making it easier to form thin-walled carbon nanotubes.
[0017] (6) The thin-walled carbon nanotubes obtained by the preparation method of the present invention have a thin-wall index δ>4, an outer diameter of the carbon nanotubes of 80-150nm, a wall thickness of 12.5-20nm, 32-50 wall layers, and an inner diameter of 55-110nm. The larger inner diameter is conducive to filling other nanomaterials; morphology: spiral shape, smooth wall; properties: magnification of 15.6-19.8 times, powder resistivity (20Mpa) of 12.35-14.72mΩ·cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Attached Figure 1 This is a low magnification SEM image of the carbon nanotube catalyst in Example 1 of the present invention.
[0019] Attached Figure 2 This is a high-magnification SEM image of the carbon nanotube catalyst in Example 2 of the present invention.
[0020] Attached Figure 3 This is the SEM image of sample 1 obtained in Example 1 of the present invention.
[0021] Attached Figure 4 This is the TEM image of sample 1 obtained in Example 1 of the present invention.
[0022] Attached Figure 5 This is a high-magnification TEM image of some carbon nanotubes in sample 1 obtained in Example 1 of the present invention.
[0023] Attached Figure 6 This is the SEM image of sample 2 obtained in Example 2 of the present invention.
[0024] Attached Figure 7 This is the TEM image of sample 2 obtained in Example 2 of the present invention.
[0025] Attached Figure 8 This is a high-magnification TEM image of some carbon nanotubes of Sample 2 obtained in Example 2 of the present invention.
[0026] Attached Fig. 9 This is the SEM image of comparative sample 1 obtained in comparative example 1 of the present invention.
[0027] Attached Fig.10This is a TEM image of comparative sample 1 obtained in comparative example 1 of the present invention.
[0028] Attached Fig.11 This is a high-magnification TEM image of a single carbon fiber in Comparative Sample 1 obtained in Comparative Example 1 of the present invention.
[0029] Attached Fig.12 This is a high-magnification TEM image of a small amount of carbon nanotubes in Comparative Sample 1 obtained in Comparative Example 1 of the present invention.
[0030] Attached Fig.13 This is the SEM image of comparative sample 2 obtained in comparative example 2 of the present invention.
[0031] Attached Fig.14 This is the TEM image of comparative sample 2 obtained in comparative example 2 of the present invention.
[0032] Attached Fig.15 This is a high-magnification TEM image of some carbon nanotubes in Comparative Sample 2 obtained in Comparative Example 2 of the present invention.
[0033] Attached Fig.16 This is the SEM image of comparative sample 3 obtained in comparative example 3 of the present invention.
[0034] Attached Fig.17 This is the TEM image of comparative sample 3 obtained in comparative example 3 of the present invention.
[0035] Attached Fig.18 This is a high-magnification TEM image of some carbon nanotubes in comparative sample 3 obtained in comparative example 3 of the present invention.
[0036] The present invention will be further described below through specific implementation modes. DETAILED DESCRIPTION
[0037] A method for preparing thin-walled carbon nanotubes of the present invention comprises the following steps:
[0038] S1. Preparing carbon nanotube catalyst precursor by sol-gel method;
[0039] S2, reducing the carbon nanotube catalyst precursor prepared in step S1 to obtain a carbon nanotube catalyst;
[0040] S3, using the carbon nanotube catalyst obtained in step S2, using one or more nitrogen-containing hydrocarbon compounds selected from acetonitrile, butyronitrile and adiponitrile as carbon sources, and adopting chemical vapor deposition to prepare thin-walled carbon nanotubes.
[0041] In step S1, the prepared carbon nanotube catalyst precursor is a metal oxide, and the steps of preparing the metal oxide by the sol-gel method are as follows:
[0042] S1.1, dissolving active metal salt, auxiliary metal salt and carrier in water, mixing evenly to obtain a metal salt solution;
[0043] S1.2, mixing the organic reagent and the metal salt solution obtained in step S1.1 uniformly to obtain a metal-containing gel solution;
[0044] S1.3, oxidizing and calcining the metal-containing gel solution obtained in step S1.2, and the obtained metal oxide is the carbon nanotube catalyst precursor.
[0045] In the above method for preparing carbon nanotube catalyst precursor: by weight, the amount of active metal salt added is 2-10 parts, the amount of auxiliary metal salt added is 0.1-1 parts, the amount of carrier added is 0.5-3 parts, the amount of organic reagent added is 1.5-7 parts, and the amount of water added is 10-18 parts.
[0046] In step S1.1, the active metal salt is: one or more of a soluble iron salt, a soluble nickel salt and a soluble cobalt salt; when the active metal salt is a soluble nickel salt and a soluble iron salt, the molar ratio of the added soluble nickel salt to the soluble iron salt is 1:(1-4); when the active metal salt is a soluble cobalt salt and a soluble iron salt, the molar ratio of the added soluble cobalt salt to the soluble iron salt is 1:(1-5).
[0047] In step S1.1, the auxiliary metal salt is one or more of ammonium molybdate tetrahydrate, copper nitrate, ammonium metavanadate, and ferric pyrophosphate. The auxiliary metal salt can give full play to the active ingredients of the active metal salt and promote the formation of the metal particle crystal phase; the carrier is one or more of magnesium oxide, aluminum oxide, diatomaceous earth, kaolin, aluminum nitrate, and magnesium nitrate.
[0048] In step S1.2, the organic reagent used is one or more of citric acid, maleic anhydride, tartaric acid, and sodium gluconate.
[0049] The sol-gel method is simple, easy to operate, and can achieve uniform dispersion of the components. In step S1.1 and step S1.2, the components are mixed evenly by stirring: the stirring rate of step S1.1 is 300-500 rpm, and the stirring time is 20-40 min; the stirring rate of step S1.2 is 400-600 rpm, and the stirring time is 2-4 h.
[0050] In step S1.3, the method for oxidative calcination of the metal-containing gel solution obtained in step S1.2 is: placing the metal-containing gel solution in a high-temperature furnace, adjusting the high-temperature furnace to heat up to 700-900°C at a rate of 5-10°C / min, then introducing air at a flow rate of 300-1000mL / min into the high-temperature furnace, and keeping the temperature for 90-180min to obtain a carbon nanotube catalyst precursor.
[0051] In step S2 of the method for preparing thin-walled carbon nanotubes of the present invention, the method for reducing the carbon nanotube catalyst precursor prepared in step S1 is: placing the carbon nanotube catalyst precursor in a high-temperature furnace, introducing nitrogen to exhaust the air, controlling the high-temperature furnace to heat up to 500-700°C at a rate of 4-8°C / min, and stopping the nitrogen flow; then introducing hydrogen at a flow rate of 100-200mL / min into the high-temperature furnace, and the time for introducing hydrogen is 10-20min, the carbon nanotube catalyst precursor is reduced, and a carbon nanotube catalyst is obtained.
[0052] In order to obtain a smaller carbon nanotube catalyst and improve the efficiency of reducing metal oxides, the carbon nanotube catalyst precursor is preferably sieved before high-temperature reduction, and finally a catalyst precursor with a mesh size of 20-100 is selected for reaction.
[0053] Among the existing methods for preparing carbon nanotubes, the preferred one is the chemical vapor deposition method (CVD), the basic principle of which is to allow the carbon source gas (such as methane, ethanol, etc.) to undergo a decomposition reaction under the action of a catalyst, and then generate carbon nanotubes on the catalyst surface. The catalyst is usually selected from transition metal elements Fe, Co, Ni and their compounds, which can reduce the activation energy of carbon nanotube generation and promote the decomposition of the carbon source gas and the growth of carbon nanotubes.
[0054] During the CVD process of preparing carbon nanotubes, the decomposition of the carbon source requires heat and time. Under the same time and heat, the metal-type carbon nanotube catalyst can quickly coat the surface with carbon and form carbon nanotubes.
[0055] Metal oxides can also be used directly as carbon nanotube catalysts, but metal oxide carbon nanotube catalysts will first absorb heat at high temperatures, then decompose oxygen atoms under the influence of hydrogen, and then carbon can be coated on the resulting metal particles and grow carbon nanotubes. Although this process effectively utilizes the hydrogen produced by the decomposition of the carbon source, this process also increases the heat and time required for the CVD method to prepare carbon nanotubes, thereby increasing the energy consumption and reaction difficulty of the CVD method.
[0056] In the preparation method of the present invention, the metal oxide is first reduced separately, and the reaction temperature is significantly lower than the temperature when the carbon nanotubes are prepared by CVD, thereby reducing the energy consumption of the overall reaction. The method is carried out separately from the CVD method and controlled separately to avoid mutual influence between the two, which is easy for industrial production.
[0057] In step S3 of the preparation method of thin-walled carbon nanotubes of the present invention, CVD method is also used for preparation. The specific method is: a protective gas is introduced into a high-temperature furnace, and when the temperature is raised to 750-950°C at a rate of 2-8°C / min, a mixed gas of reducing gas and protective gas is introduced into the high-temperature furnace, wherein the protective gas is one or more of nitrogen, argon, and helium, and the flow rate of the protective gas is 50-200mL / min; the reducing gas is hydrogen, and the flow rate of the reducing gas is 50-100mL / min. Then, a nitrogen-containing hydrocarbon compound is injected, and the injection flow rate of the nitrogen-containing hydrocarbon compound is 0.2-1mL / min. After reacting for 30-90min, the introduction of the nitrogen-containing hydrocarbon compound and the reducing gas is stopped. The flow rate of the protective gas is adjusted to 300-500mL / min, and then the temperature in the high-temperature furnace is reduced to room temperature at a rate of 2-5°C / min to obtain a thin-walled carbon nanotube with a large inner diameter.
[0058] When using chemical vapor deposition to prepare carbon nanotubes, the injection rate of nitrogen-containing hydrocarbon compounds will affect the morphology of carbon nanotubes: too low an injection rate will result in too small an inner diameter of the tube, insufficient helix angle, too many tube wall layers, and reduced magnification; too high an injection rate will cause the carbon nanotubes to grow too fast, resulting in the thickness of the tube wall being mixed and unstable. Therefore, nitrogen-containing hydrocarbon compounds are generally injected through a syringe and a wet spinning machine, and a fixed injection rate is input during application to control the feed speed.
[0059] By introducing a carbon source at high temperature: nitrogen-containing hydrocarbon compounds, the influence of the catalyst particle size and the influence of the added hydrocarbon compounds can make the catalyst particles maintain a bottom growth mode during the growth of carbon nanotubes. At the same time, because the nitrogen-containing hydrocarbon compounds decompose at high temperatures, the nitrogen element therein can change the field emission properties of the catalyst metal particles, making it easier for the carbon nanotubes grown on the catalyst particles to grow in the direction of a larger spiral angle, thereby avoiding the process of thickening of the parallel surface wall layer and making it easier to form thin-walled carbon nanotubes.
[0060] The introduction of hydrogen at high temperature can ensure the cleanliness of the thin-walled carbon nanotubes and avoid the accumulation of impurities after the activity of the catalyst particles ends, thereby forming a thicker wall layer and growing vapor-grown carbon fibers.
[0061] The advantages of the method for preparing thin-walled carbon nanotubes of the present invention are compared and analyzed through specific examples below.
[0062] Example 1
[0063] In parts by weight, 8 parts of an active metal salt consisting of nickel nitrate hexahydrate and iron nitrate nonahydrate in a molar ratio of 1:4, 0.5 parts of ammonium molybdate tetrahydrate as an auxiliary metal salt, and 2 parts of an aluminum nitrate carrier are dissolved in 18 parts of water, and stirred at a stirring speed of 400 rpm for 20 minutes to uniformly mix the active metal salt, the auxiliary metal salt, and the carrier metal salt to prepare a metal salt solution;
[0064] Mix 2 parts of citric acid and the metal salt solution uniformly, and stir at a stirring speed of 600 rpm for 2 hours to obtain a metal-containing gel solution;
[0065] The metal-containing gel solution was oxidatively calcined in a high-temperature furnace, specifically, the heating rate of the high-temperature furnace was adjusted to 10° C. / min, the temperature was raised to 800° C., air was introduced into the high-temperature furnace, the air flow rate was 600 mL / min, and the temperature was kept for 90 minutes to obtain a carbon nanotube catalyst precursor;
[0066] The catalyst precursor was sieved, and the catalyst precursor with a mesh size of 20-100 was put into a high-temperature furnace. Nitrogen was introduced to exhaust the air, and the nitrogen flow rate was 300 mL / min. The heating rate of the high-temperature furnace was controlled to be 5°C / min. When the temperature was raised to 600°C, the introduction of nitrogen was stopped. Then, hydrogen reduction gas was introduced into the high-temperature furnace, and the hydrogen flow rate was controlled to be 100 mL / min. The introduction time was 15 min. After the high-temperature calcination was completed, a carbon nanotube catalyst was obtained;
[0067] Argon gas was introduced into the high-temperature furnace at a gas flow rate of 300 mL / min, and the heating rate of the high-temperature furnace was controlled to be 8°C / min. When the temperature was raised to 850°C, a mixture of hydrogen and argon gases was introduced into the high-temperature furnace. At the same time, acetonitrile was injected through a syringe, wherein the acetonitrile flow rate was 0.2 mL / min, the argon flow rate was 50 mL / min, and the hydrogen flow rate was 50 mL / min. After reacting for 60 minutes, the introduction of acetonitrile and hydrogen was stopped, the argon gas flow rate was controlled to 300 mL / min, the temperature in the high-temperature furnace was controlled to 850°C, and then the temperature in the high-temperature furnace was lowered to room temperature at a cooling rate of 3°C / min to obtain thin-walled carbon nanotubes, which were recorded as sample 1.
[0068] The properties and morphology of sample 1 were tested, and the results showed that the magnification of thin-walled carbon nanotube sample 1 was 19.8 times, the powder resistivity (20Mpa) was 12.35mΩ·cm, and the SEM image showed a spiral carbon nanotube with a smooth and clear tube wall (see attached). Figure 3 ); Clear hollow tubes were observed under TEM (attached Figure 4 ) Figure 5It shows that the outer diameter of sample 1 is 80-120nm, the inner diameter is 55-90nm, the wall thickness is 12.5-15nm, the number of wall layers is 32-37, and the thin-wall index δ is 4.4-6, which is a thin-walled carbon nanotube.
[0069] Example 2
[0070] In parts by weight, 3 parts of an active metal salt composed of nickel nitrate hexahydrate and cobalt nitrate hexahydrate in a molar ratio of 1:1, 0.1 parts of ammonium metavanadate as an auxiliary metal salt, and 0.5 parts of an aluminum nitrate carrier are dissolved in 10 parts of water, and stirred at a stirring speed of 400 rpm for 10 minutes to uniformly mix the active metal salt, the auxiliary metal salt, and the carrier metal salt to prepare a metal salt solution;
[0071] Mix 2 parts of tartaric acid and the metal salt solution uniformly, and stir at a stirring speed of 500 rpm for 2 hours to obtain a metal-containing gel solution;
[0072] The metal-containing gel solution is placed in a high-temperature furnace for oxidative calcination. Specifically, the temperature of the high-temperature furnace is adjusted to a heating rate of 10°C / min, the temperature is raised to 750°C, air is introduced into the high-temperature furnace at an air flow rate of 500mL / min, and then the temperature is kept for 100min to obtain a catalyst precursor;
[0073] The catalyst precursor was sieved, and the catalyst precursor with a mesh size of 20-100 was put into a high-temperature furnace. Nitrogen was introduced to exhaust the air, and the nitrogen flow rate was 400 mL / min. The heating rate of the high-temperature furnace was controlled to be 6°C / min. When the temperature was raised to 700°C, the introduction of nitrogen was stopped. Then, hydrogen reduction gas was introduced into the high-temperature furnace, and the hydrogen flow rate was controlled to be 150 mL / min. The introduction time was 10 min. After the high-temperature calcination was completed, a thin-walled carbon nanotube catalyst with an ultra-large inner diameter was obtained;
[0074] Nitrogen gas was introduced into the high-temperature furnace at a gas flow rate of 250 mL / min, and the heating rate of the high-temperature furnace was controlled to be 5°C / min. When the temperature was raised to 900°C, a mixture of hydrogen and nitrogen gases was introduced into the high-temperature furnace, and adiponitrile was injected through a syringe at the same time, wherein the adiponitrile flow rate was 0.3 mL / min, the nitrogen flow rate was 80 mL / min, and the hydrogen flow rate was 50 mL / min. After reacting for 30 minutes, the introduction of adiponitrile and hydrogen was stopped, the nitrogen gas flow rate was controlled to 300 mL / min, the temperature in the high-temperature furnace was controlled to 900°C, and then the temperature in the high-temperature furnace was lowered to room temperature at a cooling rate of 5°C / min to obtain thin-walled carbon nanotubes with a large inner diameter, which were recorded as sample 2.
[0075] The properties and morphology of sample 2 were tested, and the results showed that the magnification of thin-walled carbon nanotube sample 2 was 15.6 times, the powder resistivity (20Mpa) was 14.72mΩ·cm, and the spiral carbon nanotubes were observed under SEM, and the tube wall was relatively smooth and clear (see attached). Figure 6 ), a relatively clear hollow tube was observed under TEM (attached Figure 7 ), the outer diameter of the tube is 100-150nm, the inner diameter of the tube is 70-110nm, the wall thickness is 15-20nm, and the number of wall layers is 37-50 (attached Figure 8 ), and calculated that the thin-wall index δ is 4.6-5.5, which is a thin-walled carbon nanotube.
[0076] Comparative Example 1
[0077] In parts by weight, 8 parts of an active metal salt consisting of nickel nitrate hexahydrate and iron nitrate nonahydrate in a molar ratio of 1:4, 0.5 parts of ammonium molybdate tetrahydrate as an auxiliary metal salt, and 2 parts of an aluminum nitrate carrier are dissolved in 18 parts of water, and stirred at a stirring speed of 400 rpm for 10 minutes to uniformly mix the active metal salt, the auxiliary metal salt, and the carrier metal salt to prepare a metal salt solution;
[0078] 2 parts by weight of citric acid and the metal salt solution were mixed evenly, and stirred at a stirring speed of 600 rpm for 2 hours to obtain a metal-containing gel solution;
[0079] The metal-containing gel solution is placed in a high-temperature furnace for oxidative calcination. Specifically, the temperature of the high-temperature furnace is adjusted to a rate of 10°C / min, the temperature is raised to 900°C, air is introduced into the high-temperature furnace at an air flow rate of 500mL / min, and then the temperature is kept for 100min to obtain a catalyst precursor;
[0080] The catalyst precursor was sieved, and the catalyst precursor with a mesh size of 20-100 was put into a high-temperature furnace. Nitrogen was introduced to exhaust the air, and the nitrogen flow rate was 400 mL / min. The heating rate of the high-temperature furnace was controlled to be 6°C / min. When the temperature was raised to 700°C, the introduction of nitrogen was stopped. Then, hydrogen reduction gas was introduced into the high-temperature furnace, and the hydrogen flow rate was controlled to be 150 mL / min. The introduction time was 10 min. After the high-temperature calcination was completed, a thin-walled carbon nanotube catalyst with an ultra-large inner diameter was obtained;
[0081] Nitrogen was introduced into the high-temperature furnace at a gas flow rate of 250 mL / min, and the heating rate of the high-temperature furnace was controlled to be 5°C / min. When the temperature was raised to 900°C, a mixture of methane, hydrogen and nitrogen was introduced into the high-temperature furnace, wherein the methane flow rate was 100 mL / min, the nitrogen flow rate was 50 mL / min, and the hydrogen flow rate was 50 mL / min. After reacting for 60 minutes, the introduction of methane and hydrogen was stopped, the nitrogen gas flow rate was controlled to 300 mL / min, the temperature in the high-temperature furnace was controlled to 900°C, and then the temperature in the high-temperature furnace was lowered to room temperature at a cooling rate of 3°C / min to obtain multi-walled carbon nanotubes, which were recorded as comparison sample 1.
[0082] The results of the comparative sample 1 are as follows: the magnification of the comparative sample 1 is 2.1 times, the powder resistivity (20Mpa) is 19.88mΩ·cm, and the bamboo-like carbon nanotubes are observed under SEM, and the tube wall is relatively rough (see attached Fig. 9 ); A small number of hollow tubes were observed under TEM, and most of the rest were solid tubes without tube wall structure. The outer diameter of the tube was 200-500nm, which was vapor-grown carbon fiber (attached Fig.10 , Attachment Fig.11 ); In addition, a small number of hollow tubes were measured, such as the attached Fig.12 The outer diameter of the hollow tube is 20-100 nm, the inner diameter is 5-18 nm, the wall thickness is 7.5-41 nm, the number of wall layers is 18-102, and the calculated thin-wall index δ is 0.4-0.7, which is an ordinary carbon nanotube.
[0083] Comparative Example 2
[0084] By weight, 8 parts of an active metal salt composed of nickel nitrate hexahydrate and iron nitrate nonahydrate in a molar ratio of 1:4, 0.5 parts of ammonium molybdate tetrahydrate as an auxiliary metal salt, and 2 parts of an aluminum nitrate carrier are dissolved in 18 parts of water, and stirred at a stirring speed of 400 rpm for 10 minutes to uniformly mix the active metal salt, the auxiliary metal salt, and the carrier metal salt to prepare a metal salt solution;
[0085] 2 parts by weight of citric acid and the above metal salt solution were mixed evenly, and stirred at a stirring speed of 600 rpm for 2 hours to obtain a metal-containing gel solution;
[0086] The metal-containing gel solution is placed in a high-temperature furnace for oxidative calcination. Specifically, the temperature of the high-temperature furnace is adjusted to a heating rate of 10°C / min, the temperature is raised to 800°C, air is introduced into the high-temperature furnace at an air flow rate of 500mL / min, and then the temperature is kept for 100min to obtain a catalyst precursor;
[0087] The catalyst precursor was sieved, and the catalyst precursor with a mesh size of 20-100 was put into a high-temperature furnace. Nitrogen was introduced to exhaust the air, and the nitrogen flow rate was 400 mL / min. The heating rate of the high-temperature furnace was controlled to be 6°C / min. When the temperature was raised to 700°C, the introduction of nitrogen was stopped. Then, hydrogen reduction gas was introduced into the high-temperature furnace, and the hydrogen flow rate was controlled to be 150 mL / min. The introduction time was 10 min. After the high-temperature calcination was completed, a thin-walled carbon nanotube catalyst with an ultra-large inner diameter was obtained;
[0088] Nitrogen was introduced into the high-temperature furnace at a gas flow rate of 250 mL / min, and the heating rate of the high-temperature furnace was controlled to be 5°C / min. When the temperature was raised to 850°C, a mixture of hydrogen and nitrogen was introduced into the high-temperature furnace, and ethanol was injected with a syringe at the same time, wherein the ethanol flow rate was 0.2 mL / min, the nitrogen flow rate was 50 mL / min, and the hydrogen flow rate was 50 mL / min. After reacting for 60 minutes, the introduction of ethanol and hydrogen was stopped, the nitrogen gas flow rate was controlled to 300 mL / min, the temperature in the high-temperature furnace was controlled to 850°C, and then the temperature in the high-temperature furnace was lowered to room temperature at a cooling rate of 3°C / min to obtain multi-walled carbon nanotubes, which were recorded as comparison sample 2.
[0089] The comparison sample 2 was tested and found to have a magnification of 3.6 times, a powder resistivity (20Mpa) of 18.11mΩ·cm, and straight columnar and bamboo-shaped carbon nanotubes were observed under SEM. The tube wall was relatively rough (see attached). Fig.13 ), attached Fig.14 A small number of solid tubes were observed in the TEM image, without tube wall structure, and the outer diameter of the tube was 100-300nm, which was the vapor-grown carbon fiber; the rest were mostly hollow tubes, as shown in the attached Fig.15 As shown: the outer diameter of the hollow tube is 20-90nm, the inner diameter of the tube is 10-40nm, the wall thickness is 5-25nm, the number of wall layers is 12-62, and the calculated thin-wall index δ is 1.6-2, which is an ordinary carbon nanotube.
[0090] Comparative Example 3
[0091] In parts by weight, 10 parts of an active metal salt composed of nickel nitrate hexahydrate and iron nitrate nonahydrate in a molar ratio of 1:7, 1.5 parts of ammonium molybdate tetrahydrate as an auxiliary metal salt, and 4 parts of an aluminum nitrate carrier are dissolved in 20 parts of water, and stirred at a stirring speed of 400 rpm for 10 minutes to uniformly mix the active metal salt, the auxiliary metal salt, and the carrier metal salt to prepare a metal salt solution;
[0092] 8 parts by weight of citric acid and the metal salt solution were mixed uniformly, and stirred at a stirring speed of 600 rpm for 2 hours to obtain a metal-containing gel solution;
[0093] The metal-containing gel solution is placed in a high-temperature furnace for oxidative calcination. Specifically, the temperature of the high-temperature furnace is adjusted to a heating rate of 10°C / min, the temperature is raised to 800°C, air is introduced into the high-temperature furnace at an air flow rate of 500mL / min, and then the temperature is kept for 100min to obtain a catalyst precursor;
[0094] The catalyst precursor was sieved, and the catalyst precursor with a mesh size of 20-100 was put into a high-temperature furnace. Nitrogen was introduced to exhaust the air, and the nitrogen flow rate was 400 mL / min. The heating rate of the high-temperature furnace was controlled to be 6°C / min. When the temperature was raised to 700°C, the introduction of nitrogen was stopped. Then, hydrogen reduction gas was introduced into the high-temperature furnace, and the hydrogen flow rate was controlled to be 150 mL / min. The introduction time was 10 min. After the high-temperature calcination was completed, a thin-walled carbon nanotube catalyst with an ultra-large inner diameter was obtained;
[0095] Nitrogen gas was introduced into the high-temperature furnace at a gas flow rate of 250 mL / min, and the heating rate of the high-temperature furnace was controlled to be 5°C / min. When the temperature was raised to 850°C, a mixture of hydrogen and nitrogen gases was introduced into the high-temperature furnace, and acetonitrile was injected with a syringe at the same time, wherein the acetonitrile flow rate was 0.2 mL / min, the nitrogen flow rate was 50 mL / min, and the hydrogen flow rate was 50 mL / min. After reacting for 60 minutes, the introduction of acetonitrile and hydrogen was stopped, the nitrogen gas flow rate was controlled to 300 mL / min, the temperature in the high-temperature furnace was controlled to 850°C, and then the temperature in the high-temperature furnace was lowered to room temperature at a cooling rate of 3°C / min to obtain multi-walled carbon nanotubes, which were recorded as comparison sample 3.
[0096] The comparison sample 3 was tested and found to have a magnification of 22.5 times, a powder resistivity (20Mpa) of 19.67mΩ·cm, and carbon nanotubes of different diameters were observed under SEM. The tube wall was relatively rough (see attached). Fig.16 ), attached Fig.17 In the TEM image, a small number of solid tubes were observed, without tube wall structure, and the outer diameter of the tube was 200-600nm, which was the vapor-grown carbon fiber; the rest were mostly hollow tubes, as shown in the attached Fig.18 As shown: the outer diameter of the hollow tube is 20-140nm, the inner diameter of the tube is 8-46nm, the wall thickness is 6-47nm, the number of wall layers is 15-117, and the calculated thin-wall index δ of the hollow tube is 0.9-1.3, which is an ordinary carbon nanotube.
[0097] The properties and morphologies of the carbon nanotube samples obtained in the above Examples 1-2 and Comparative Examples 1-3 are compared, as shown in Table 1.
[0098] Table 1 Comparison of properties and morphology of carbon nanotube samples
[0099]
[0100] From the analysis of Table 1, it can be seen that: (1) the carbon nanotubes (sample 1 and sample 2) obtained by the preparation method of the present invention have a thin-wall index greater than 4, which meets the requirements of thin-walled carbon nanotubes; (2) and the inner diameters of sample 1 and sample 2 are 55-90nm and 70-110nm, respectively, both of which are large inner diameter thin-walled carbon nanotubes, suitable for filling other functional materials, and for preparing energy storage materials or other composite materials with specific uses, which provides the necessary conditions for the application development of carbon nanotubes.
[0101] By comparing the comparison sample 1 and the comparison sample 2, it can be known that: the amount of carbon source (in the comparison sample 1, methane is the carbon source, 6000mL is used, and the amount of carbon atom is 96mol; in the comparison sample 2, ethanol is the carbon source, 12mL is used, and the amount of carbon atom is 0.552mol) has a great influence on the morphology of carbon nanotubes: with an appropriate amount of carbon source, a large proportion of carbon nanotubes is formed; with a large amount of carbon source, a large proportion of carbon fibers is formed.
[0102] By comparing sample 1 and comparative sample 2, it can be seen that the difference in carbon source significantly affects the morphology of carbon nanotubes. The present invention uses nitrogen-containing hydrocarbon compounds as carbon sources to obtain thin-walled carbon nanotubes with relatively regular morphology.
[0103] In comparative sample 3, except that the amount of carbon source is the same as that of sample 1, the amount of raw materials used to prepare the carbon nanotube catalyst is more than that of sample 1; and the amount and composition of the main raw material active metal salt are the same, but the molar ratio is different (sample 1 is: the molar ratio of nickel nitrate to iron nitrate is 1:4; comparative sample 3 is: the molar ratio of nickel nitrate to iron nitrate is 1:7). According to the comparison of the product morphology and physical properties of comparative sample 3 and sample 1, it can be seen that the growth of thin-walled carbon nanotubes is affected by the carbon nanotube catalyst. The carbon nanotube catalyst obtained according to the proportion of the raw materials of the present invention is flaky under macroscopic view (attached Figure 1 ), and the microscopic structure is porous (attached Figure 2 ), suitable for preparing thin-walled carbon nanotubes.
Claims
1. A method for preparing thin-walled carbon nanotubes, characterized in that: The preparation method comprises the following steps: S1. Preparing carbon nanotube catalyst precursor by sol-gel method; S2, reducing the carbon nanotube catalyst precursor prepared in step S1 to obtain a carbon nanotube catalyst; S3, using the carbon nanotube catalyst obtained in step S2 to prepare thin-walled carbon nanotubes by chemical vapor deposition; In the step S1, the prepared carbon nanotube catalyst precursor is a metal oxide; In the step S3, when the carbon nanotubes are prepared by chemical vapor deposition, the carbon source used is: nitrogen-containing hydrocarbon compounds.
2. The method for preparing thin-walled carbon nanotubes according to claim 1, characterized in that: In the step S3, the nitrogen-containing hydrocarbon compound used is one or more of acetonitrile, butyronitrile and adiponitrile.
3. The method for preparing thin-walled carbon nanotubes according to claim 1, characterized in that: In the step S1, the steps of preparing the carbon nanotube catalyst precursor by the sol-gel method are as follows: S1.1, dissolving active metal salt, auxiliary metal salt and carrier in water, mixing evenly to obtain a metal salt solution; S1.2, mixing the organic reagent and the metal salt solution obtained in step S1.1 uniformly to obtain a metal-containing gel solution; S1.3, oxidatively calcining the metal-containing gel solution obtained in step S1.2 to obtain a carbon nanotube catalyst precursor.
4. The method for preparing thin-walled carbon nanotubes according to claim 3, characterized in that: In the step S1.1, the active metal salt is one or more of a soluble iron salt, a soluble nickel salt, and a soluble cobalt salt; The auxiliary metal salt is one or more of ammonium molybdate tetrahydrate, copper nitrate, ammonium metavanadate, and ferric pyrophosphate; The carrier is one or more of magnesium oxide, aluminum oxide, diatomaceous earth, kaolin, aluminum nitrate, and magnesium nitrate; In step S1.2, the organic reagent is one or more of citric acid, maleic anhydride, tartaric acid, and sodium gluconate.
5. The method for preparing thin-walled carbon nanotubes according to claim 3 or 4, characterized in that: In the step S1, by weight, the amount of active metal salt added is 2-10 parts, the amount of auxiliary metal salt added is 0.1-1 parts, the amount of carrier added is 0.5-3 parts, the amount of organic reagent added is 1.5-7 parts, and the amount of water added is 10-18 parts.
6. The method for preparing thin-walled carbon nanotubes according to claim 4, characterized in that: When the active metal salt is a soluble nickel salt and a soluble iron salt, the molar ratio of the added soluble nickel salt to the soluble iron salt is 1:(1-4); Or when the active metal salt is a soluble cobalt salt and a soluble iron salt, the molar ratio of the added soluble cobalt salt to the soluble iron salt is 1:(1-5).
7. The method for preparing thin-walled carbon nanotubes according to claim 3, characterized in that: In the step S1.3, the method for oxidative calcination of the metal-containing gel solution obtained in the step S1.2 is: placing the metal-containing gel solution in a high-temperature furnace, adjusting the high-temperature furnace to heat up to 700-900°C at a rate of 5-10°C / min, then introducing air at a flow rate of 300-1000mL / min into the high-temperature furnace, and keeping the temperature for 90-180min to obtain a carbon nanotube catalyst precursor.
8. The method for preparing thin-walled carbon nanotubes according to claim 1, characterized in that: In the step S2, the method for reducing the carbon nanotube catalyst precursor prepared in the step S1 is: The carbon nanotube catalyst precursor is placed in a high-temperature furnace, nitrogen is introduced to exhaust the air, the high-temperature furnace is controlled to heat up to 500-700°C at a rate of 4-8°C / min, and the nitrogen is stopped; then hydrogen is introduced into the high-temperature furnace at a flow rate of 100-200mL / min for 10-20min, the carbon nanotube catalyst precursor is reduced, and a carbon nanotube catalyst is obtained.
9. The method for preparing thin-walled carbon nanotubes according to claim 1, characterized in that: In step S3, the method for preparing thin-walled carbon nanotubes by chemical vapor deposition is: A protective gas is introduced into the high-temperature furnace, and when the temperature is raised to 750-950°C at a rate of 2-8°C / min, a mixed gas of reducing gas and protective gas is introduced into the high-temperature furnace; then, a nitrogen-containing hydrocarbon compound is injected at a flow rate of 0.2-1mL / min, and after reacting for 30-90min, the introduction of the nitrogen-containing hydrocarbon compound and the reducing gas is stopped; the flow rate of the protective gas is adjusted to 300-500mL / min, and then the temperature in the high-temperature furnace is lowered to room temperature at a rate of 2-5°C / min to obtain thin-walled carbon nanotubes.
10. The method for preparing thin-walled carbon nanotubes according to claim 8, characterized in that: In the step S3, when a mixed gas of reducing gas and protective gas is introduced into the high-temperature furnace, the flow rate of the protective gas is 50-200 mL / min; the flow rate of the reducing gas is 50-100 mL / min; the reducing gas is hydrogen; the protective gas is one or more of nitrogen, argon and helium.